Intellectual Functioning in Children with Congenital Heart Defects Treated with Surgery or by Catheter Interventions - Ryberg, Carmen; Sunnegårdh, Jan; Thorson, Maria; Broberg, Malin (Frontiers in Pediatrics, 2016)
Background: Studies suggest that children with congenital heart defects (CHD) are at risk for adverse intellectual functioning. However, factors related to lower intellectual functioning in this group are largely unknown. This study describes intellectual functioning in children with CHD in relation to severity of the heart defect, the child´s age and the socioeconomic status of the family (SES). Methods: 228 children treated with surgery or by catheter technique were tested using the Wechsler intelligence scales to determine Full Scale IQ (FSIQ). FSIQ was then analyzed in relation to age (3- 5- , 9-, and 15-year-olds), severity of the diagnosis (mild, moderate, and severe), and SES (low, medium, and high). The median age was 70 months (5.8 years) with a range of 162 months (30 months (2.5 years) to 192 months (16.0 years)). Results: The total mean score on FSIQ was 100.8 (SD = 14.5). Children with severe CHD had significantly lower FSIQ than children with mild and moderate CHD, and 9- and 15-year-olds had significantly lower FSIQ compared to the 3-year-olds. Children from families with low SES had significantly lower FSIQ than children from medium SES and high SES families. No interaction between severity of diagnosis, age, and SES was found for FSIQ. Conclusions: 83% of the children with CHD performed at or above average with respect to FSIQ. SES and severity of diagnosis had significant main effects on FSIQ. These factors should be considered when planning interventions and follow-up programs for children with CHD.